ETHICAL PERSPECTIVES OF SUSTAINABLE USE OF REEF’S INVERTEBRATES AS A SOURCE OF MARINE NATURAL PRODUCTS - S Sukarmi; Agus Sabdono (JOURNAL OF COASTAL DEVELOPMENT, 2008)
Among marine animals, reef’s invertebrates are the most prolific producers of secondary metabolites and have become sources of great interest to natural product chemistry, since they provide a large proportion of bioactive compounds with different biological activities. Supply’s problem has hampered the investigation of secondary metabolites from marine invertebrates, and many highly active compounds produced contribute to<10-6 % of the body-wet weight. Providing sufficient amounts of these biologically active substances, hence, may be a difficult task. In addition, it has often proven extremely difficult, and some cases impossible, to provide from invertebrates sufficient amounts of many of these substances due to limited amounts found in the producing organism, or to limited quantity of the organism itself, or to geographic, seasonal or sexual variations in the amounts and in the nature of produced secondary metabolites. There has an increasing concerns regarding the collecting reef’s organisms for the discovery and development of pharmaceuticals since it has been perceived variously as sustaining and threatening conservation. There is an urgent need to take into account the bioethical considerations in anticipating the potential consequences of these activities and proposing management options for sustainable use of reef’s invertebrates as the sources of bioactive compounds.